A novel set of microsatellite markers for the European Grapevine Moth Lobesia botrana isolated using next-generation sequencing and their utility for genetic characterization of populations from Europe and the Middle East. Issue 4 (8th April 2015) - Reineke, A.; Assaf, H.A.; Kulanek, D.; Mori, N.; Pozzebon, A.; Duso, C.
Abstract: Using a high-throughput 454 pyrosequencing approach a novel set of microsatellite markers was developed for one of the key grapevine insect pests, the European grapevine moth Lobesia botrana (Lepidoptera: Tortricidae). 20 primer pairs flanking a microsatellite motif were designed based on the sequences obtained and were subsequently evaluated in a sample of 14 L. botrana populations from Europe and the Middle East. 11 markers showed stable and reproducible amplification patterns; however, one of the 11 markers was monomorphic in all L. botrana populations analysed. Estimated frequencies of null alleles of more than 20% were evident for two of the markers tested, but varied substantially depending on the respective L. botrana population. In 12 of the 14 L. botrana populations observed heterozygosities were lower to those expected under Hardy–Weinberg equilibrium, indicating a deficiency of heterozygotes in the respective populations. The overall F ST value of 0.075 suggested a moderate but significant genetic differentiation between the L. botrana populations included in this study. In addition, a clear geographic structure was detected in the set of samples, evident through a significant isolation by distance and through results from structure analysis. In structure analysis, L. botrana populations were grouped in two clearly separated clusters according to their European (Spain, Italy, Germany) or Middle Eastern (Israel, Syria, Turkey) origin. This novel set of microsatellite markers can now be applied to study the evolutionary ecology of this species including host shifts and host adaptation as well as spread of individuals across worldwide viticulture.